Urgensi nilai–nilai Al–quran dalam pendidikan dasar madrasah ibtidaiyah - Yassaro, Fierly Sabila (Maliki Interdisciplinary Journal, 2025)
The Qur'an is the holy book of Muslims which is guaranteed to be holy until the last day. The Quran is the main source of Islamic teachings as well as a guide for daily life, including in the fields of education and learning. The urgency of the values contained in it is very instrumental in character building and also learning for students. The Qur'an is a pillar for Islamic-based education that aims to produce students with character and good character. The special stories contained in the Koran can motivate students to always do good, both to themselves and others. Therefore, in this article, the author will explain the urgency of the values of the Koran in madrasah ibtidaiyah education, its benefits and its implementation.